PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAU DAN DAK TERHADAP ALOKASI BELANJA MODAL DENGAN LUAS WILAYAH SEBAGAI VARIABEL MODERASI PADA PEMERINTAH KABUPATEN / KOTA PROVINSI BANTEN - Oktavia, Bella Rafti; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
The focus of this study was to evaluate the influence of taxes, retribution, General Allocation Fund (DAU), and Special Allocation Fund (DAK), on the government's capital spending in the province of Banten. Building upon previous research limitations, the study included the geographical area as a moderating factor in the connection between the independent and dependent variables. Utilizing a quantitative descriptive method and secondary data regression analysis of the budget reports from the local government of Banten spanning 2018 to 2022, this research delved into the collective analysis of the relationship between local revenue variables and capital expenditure. The research specifically examined how the area's expanse influenced this relationship.The results suggested that municipal taxes, retribution, and special allocation funds had no significant impact on capital spending. Nevertheless, the General Allocation Fund had a significant effect on capital expenditure to some extent. Furthermore, it has been demonstrated that the size of the region has a significant role in influencing the link between local revenue factors and capital expenditure at the same time.